Cognitive liberty and the psychedelic humanities - González Romero, Osiris (Frontiers in Psychology, 2023)
Abstract This research aims to conceptualize cognitive liberty and the psychedelic humanities by examining their constitutive elements. The importance of this study lies in the fact that it is widespread to talk about psychedelic science nowadays, but there is a significant gap in the research. For instance, the role and importance of the humanities need to be acknowledged. Regarding cognitive liberty, this research considers that people have the right to use or refrain from using emerging neurotechnologies and psychedelics. People´s freedom of choice vis-à-vis these technologies must be protected, in particular with regard to coercive and non-consensual uses. Firstly, an analysis will be carried out of the constitutive elements of cognitive liberty, especially within the context of a philosophical approach. Secondly, this research will address some arguments for the philosophical uses of psychedelics. Finally, this paper will discuss the scope and significance of psychedelic humanities as a vein of research. Cognitive liberty is a crucial concept for the psychedelic humanities, likely to broaden our understanding of consciousness studies and reflect on ethical and social issues related to scientific research. Cognitive liberty is an update of freedom of thought according to the challenges of the 21st century. In addition, this paper will highlight the possible philosophical uses of psychedelic substances to broaden the research scope since, at present, the ritual and therapeutic uses of psychedelics have the most significant legitimacy. Recognition of philosophical uses demonstrates that learning from non-clinical uses of psychedelics is possible. The psychedelic humanities represent an underexplored avenue of research that can contribute to a better understanding of the interplay between science and culture.